What are the advantages and disadvantages of a zero trust model? (O'Reilly, 2017)
"Zero trust networks are an evolution of current security models; but why should you care, and how can they help you? In this video Doug Barth and Evan Gilman will give you an overview of the advantages that a zero trust model can offer your organization; as well as the disadvantages that you will have to overcome to implement them."--Resource description page